Vocational profile of applicants in educational programs: interests and aptitudes - Sunza Chan, Sandra Paola; Ramírez de Arellano De la Peña, Jorge Alberto; Martín Pavón, Mario José (IE Revista de Investigación Educativa de la REDIECH, 2023)
This research aims to analyze the vocational profile of high school students from the State of Yucatán who expressed the aspiration to pursue programs in the field of education, in order to identify the congruence of their interests and aptitudes with the requirements of this area, in comparison with the characteristics of applicants from other programs. A quantitative, comparative, and cross-sectional research was chosen, with the participation of 2,587 students in their last year of high school, who answered a questionnaire focused on socio-educational aspects, interests and vocational aptitudes. The results showed higher indicators of socio-educational vulnerability in applicants to education programs than in those who opt for other professions; likewise, it was found that they have more interests and aptitudes from the profile of an education professional, in comparison with those who aspire to other areas. The findings allow to draw conclusions about the need to incorporate educational policies aimed at social justice, focusing on the characteristics of vulnerability of students who intend to train in the educational field, also that it is necessary to strengthen the recruitment and selection processes of future professionals of education who have the ideal vocational profile to perform in the different...